Bell's Palsy as a Potential Predictor Factor for Stroke: A Systematic Literature Review - Gosal, Indra Febryan; Ulfa, Nurul Nisa; Sembiring, Dewanta (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Bell's palsy, which is caused by herpes simplex virus type 1 (HSV-1) and varicella-zoster virus (VZV), can be a marker for stroke. This study aims to identify and explain the potential of Bell's palsy as a predictor factor for stroke. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding Bell’s palsy and stroke. The search was performed using the terms: (1)